Teacher Collaboration in Overcoming Learning Mathematics - Fajriah, Siti; Syukur, Yarmis (Jurnal Aplikasi IPTEK Indonesia, 2022)
In efforts to achieve the goals of learning Mathematics there are various problems that make the learning objectives not optimally achieved, one of which is due to difficulties in learning Mathematics. Indicators for determining student learning difficulties are students not being able to master the subject matter in accordance with the allotted time, students obtaining low learning achievement ratings compared to other students and students not being able to achieve learning achievements according to their abilities, this requires collaboration from the teacher BK and Mathematics teachers in overcoming it. This research uses a qualitative approach with a descriptive type. The subjects in this study were counseling teachers, math teachers and 2 class XI students. Data collection techniques used are observation, interviews and documentation studies. Data were analyzed through several stages, namely data collection, data reduction, data presentation and data verification. The results of this study indicate that there is collaboration between the counseling teacher and the mathematics teacher in alleviating students' learning difficulties. The establishment of close collaboration between the two parties, students not only overcome their problems but students can develop fully and optimally.